2014
DOI: 10.1021/nl5034304
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Nanorod–Carbon Nanotube Biomimetic Films for Wire-Free Photostimulation of Blind Retinas

Abstract: We report the development of a semiconductor nanorod-carbon nanotube based platform for wire-free, light induced retina stimulation. A plasma polymerized acrylic acid midlayer was used to achieve covalent conjugation of semiconductor nanorods directly onto neuro-adhesive, three-dimensional carbon nanotube surfaces. Photocurrent, photovoltage, and fluorescence lifetime measurements validate efficient charge transfer between the nanorods and the carbon nanotube films. Successful stimulation of a light-insensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(120 citation statements)
references
References 54 publications
6
114
0
Order By: Relevance
“…In contrast, other neuromodulation techniques, which are free of genetic modification, have been developed using photovoltaic and photothermal mechanisms. Photoelectric methods stimulate neurons by generating photocurrents, and it has been reported that photovoltaic materials or photoconductive materials can be used to stimulate retinal ganglion cells [3,4] or cultured neurons [5,6]. Photothermal stimulation is a new method to modulate neural activity by generating heat locally at the periphery of the cell through external light and provide either excitatory or inhibitory stimulus to the cell.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other neuromodulation techniques, which are free of genetic modification, have been developed using photovoltaic and photothermal mechanisms. Photoelectric methods stimulate neurons by generating photocurrents, and it has been reported that photovoltaic materials or photoconductive materials can be used to stimulate retinal ganglion cells [3,4] or cultured neurons [5,6]. Photothermal stimulation is a new method to modulate neural activity by generating heat locally at the periphery of the cell through external light and provide either excitatory or inhibitory stimulus to the cell.…”
Section: Introductionmentioning
confidence: 99%
“…This work illustrates the first approach to the spatiotemporal remote control of the biological reactions of C. elegans by using an artificial nanobiomachine,which exhibits the attractive features of the physicochemical properties of CNTs and liposomes.The application of this technology to abroad range of sensory systems,s uch as visual organs, [27] the auditory apparatus, [28] and thermal sensations, [22,29] is easily foreseeable.Inaddition, the use of biological tissue-permeable NIR lasers would be beneficial for remote and non-invasive inhibition and/or stimulation of aw ide range of biological targets. Furthermore,t he nanohybrids facilitated the generation of heat for the controlled-release of substrates from their nanoconstructs when irradiated with aNIR laser.…”
Section: Methodsmentioning
confidence: 99%
“…A schematic diagram of nanoparticle‐enhanced optical stimulation is shown in Figure C. Commonly used nanomaterials for enhanced optical stimulation include gold nanorods, quantum dots, and upconverting nanoparticles . Gold nanorods offer the potential to enhance techniques such as INS by absorbing irradiated energy and increasing the localization of optical stimuli .…”
Section: Biophysics Of Light–tissue Interactionsmentioning
confidence: 99%
“…A feasibility study is the evaluation of a proposed system to determine if it is technically practical. The feasibility of using optical stimulation to modulate neural activity has been rigorously proven in vitro, in vivo, in freely behaving animals, and in different animal models …”
Section: Feasibilitymentioning
confidence: 99%
See 1 more Smart Citation